2023
DOI: 10.1007/s10389-023-01826-3
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, practice and associated factors towards COVID-19 and its prevention measures among residents of Mekelle City, Tigray Region, Northern Ethiopia: a community-based cross sectional study

Abstract: Aim The emerging respiratory disease known as the novel coronavirus disease (COVID-19) became a global concern and was declared as a global health emergency by the World Health Organization (WHO) on March 11, 2022. This study aimed to assess knowledge, attitude, and practice and associated factors toward COVID-19 and its prevention measures among residents of Mekelle city, Tigray, Northern Ethiopia. Subject and methods A community-based cross-sectional study was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Mekelle owns one specialized hospital, two general hospitals, one primary hospital, and five health centers. 25 , 29 The study was conducted among randomly selected four public health facilities through a simple random sampling (lottery) method due to resource scarcity to encompass all.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mekelle owns one specialized hospital, two general hospitals, one primary hospital, and five health centers. 25 , 29 The study was conducted among randomly selected four public health facilities through a simple random sampling (lottery) method due to resource scarcity to encompass all.…”
Section: Methodsmentioning
confidence: 99%
“… 24 In Ethiopia, around 39 million diarrheal episodes occur every year, of which 230 thousand children die because of it. 25 The prevalence of Campylobacter species among under-five children with diarrhea is around 14.5% of which Campylobacter jejuni and Campylobacter coli account for 71.1% and 21.1%, respectively. 26–28 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the study done in Ethiopia, the level of knowledge (41.3%) and desirable COVID-19 practices among visitors to the Jimma University Medical Center were insufficient to combat this rapidly spreading virus [ 33 ]. Another study done to assess the knowledge, attitude, and practice towards COVID-19 among the general population revealed that the study participants' practice and attitude were poor, which will affect combating the pandemic [ 34 ]. Several other studies have been carried out to assess the KAP of study participants towards COVID-19 and its prevention measures [ [33] , [34] , [35] , [36] , [37] , [38] , [39] ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study done to assess the knowledge, attitude, and practice towards COVID-19 among the general population revealed that the study participants' practice and attitude were poor, which will affect combating the pandemic [ 34 ]. Several other studies have been carried out to assess the KAP of study participants towards COVID-19 and its prevention measures [ [33] , [34] , [35] , [36] , [37] , [38] , [39] ]. According to a study [ 40 ] conducted in Ethiopia, a high incidence of inadequate awareness and poor practice for COVID-19 was found among patients with chronic diseases, accounting for 33.9% and 47.3%, respectively.…”
Section: Introductionmentioning
confidence: 99%